Corrosion-fatigue synergy in steel bridges: Mechanisms and mechanical degradation - Lizhen Huang; Li Wan; Zifan Zuo; Zhiqin Cai; Xianwei Wang; Hui Liu; Jingwen Liu (Results in Engineering, 2025)
This study pioneers the investigation of asynchronous corrosion-fatigue coupling effects on structural steel degradation, addressing a critical gap in understanding synergistic damage mechanisms under combined environmental and mechanical stresses. Through systematic experimentation under three service conditions (isolated corrosion, isolated fatigue, and asynchronous corrosion-fatigue coupling), key innovations include: (1) Quantification of a two-stage corrosion kinetics regime influenced by protective oxide layer formation; (2) Identification of an initial mechanical strengthening phase followed by progressive degradation, with yield strength showing 50 % reduction post-corrosion in coupled conditions; (3) Discovery of fatigue-induced ductility enhancement concurrent with strength loss in asynchronous coupling scenarios. These findings establish new mechanistic insights into time-dependent corrosion-fatigue interactions, providing a paradigm shift for predictive maintenance and corrosion-resistant design in steel bridge engineering.